(7p+8)(2p-3)=9p+5

Simple and best practice solution for (7p+8)(2p-3)=9p+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7p+8)(2p-3)=9p+5 equation:


Simplifying
(7p + 8)(2p + -3) = 9p + 5

Reorder the terms:
(8 + 7p)(2p + -3) = 9p + 5

Reorder the terms:
(8 + 7p)(-3 + 2p) = 9p + 5

Multiply (8 + 7p) * (-3 + 2p)
(8(-3 + 2p) + 7p * (-3 + 2p)) = 9p + 5
((-3 * 8 + 2p * 8) + 7p * (-3 + 2p)) = 9p + 5
((-24 + 16p) + 7p * (-3 + 2p)) = 9p + 5
(-24 + 16p + (-3 * 7p + 2p * 7p)) = 9p + 5
(-24 + 16p + (-21p + 14p2)) = 9p + 5

Combine like terms: 16p + -21p = -5p
(-24 + -5p + 14p2) = 9p + 5

Reorder the terms:
-24 + -5p + 14p2 = 5 + 9p

Solving
-24 + -5p + 14p2 = 5 + 9p

Solving for variable 'p'.

Reorder the terms:
-24 + -5 + -5p + -9p + 14p2 = 5 + 9p + -5 + -9p

Combine like terms: -24 + -5 = -29
-29 + -5p + -9p + 14p2 = 5 + 9p + -5 + -9p

Combine like terms: -5p + -9p = -14p
-29 + -14p + 14p2 = 5 + 9p + -5 + -9p

Reorder the terms:
-29 + -14p + 14p2 = 5 + -5 + 9p + -9p

Combine like terms: 5 + -5 = 0
-29 + -14p + 14p2 = 0 + 9p + -9p
-29 + -14p + 14p2 = 9p + -9p

Combine like terms: 9p + -9p = 0
-29 + -14p + 14p2 = 0

Begin completing the square.  Divide all terms by
14 the coefficient of the squared term: 

Divide each side by '14'.
-2.071428571 + -1p + p2 = 0

Move the constant term to the right:

Add '2.071428571' to each side of the equation.
-2.071428571 + -1p + 2.071428571 + p2 = 0 + 2.071428571

Reorder the terms:
-2.071428571 + 2.071428571 + -1p + p2 = 0 + 2.071428571

Combine like terms: -2.071428571 + 2.071428571 = 0.000000000
0.000000000 + -1p + p2 = 0 + 2.071428571
-1p + p2 = 0 + 2.071428571

Combine like terms: 0 + 2.071428571 = 2.071428571
-1p + p2 = 2.071428571

The p term is -1p.  Take half its coefficient (-0.5).
Square it (0.25) and add it to both sides.

Add '0.25' to each side of the equation.
-1p + 0.25 + p2 = 2.071428571 + 0.25

Reorder the terms:
0.25 + -1p + p2 = 2.071428571 + 0.25

Combine like terms: 2.071428571 + 0.25 = 2.321428571
0.25 + -1p + p2 = 2.321428571

Factor a perfect square on the left side:
(p + -0.5)(p + -0.5) = 2.321428571

Calculate the square root of the right side: 1.5236235

Break this problem into two subproblems by setting 
(p + -0.5) equal to 1.5236235 and -1.5236235.

Subproblem 1

p + -0.5 = 1.5236235 Simplifying p + -0.5 = 1.5236235 Reorder the terms: -0.5 + p = 1.5236235 Solving -0.5 + p = 1.5236235 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + p = 1.5236235 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + p = 1.5236235 + 0.5 p = 1.5236235 + 0.5 Combine like terms: 1.5236235 + 0.5 = 2.0236235 p = 2.0236235 Simplifying p = 2.0236235

Subproblem 2

p + -0.5 = -1.5236235 Simplifying p + -0.5 = -1.5236235 Reorder the terms: -0.5 + p = -1.5236235 Solving -0.5 + p = -1.5236235 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '0.5' to each side of the equation. -0.5 + 0.5 + p = -1.5236235 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + p = -1.5236235 + 0.5 p = -1.5236235 + 0.5 Combine like terms: -1.5236235 + 0.5 = -1.0236235 p = -1.0236235 Simplifying p = -1.0236235

Solution

The solution to the problem is based on the solutions from the subproblems. p = {2.0236235, -1.0236235}

See similar equations:

| (-362)+421= | | 8+3a=17 | | 4n+11-6n+8m=36 | | -6s=6s-144 | | x-(-19)=-20 | | 3(x-9)-4(3x+1)=x-33 | | 15x-7=8x | | b^4-16a^4=0 | | 3x-6y=-6x+34 | | 4.7x-5.48=11.44 | | (K+2)(6k-7)=0 | | x=ax+1a+bx-2b | | 12-3x+9x=14+6x | | 5x^2+4xy+2y^2=6 | | 3d-274d+10c=120 | | 2x=17x+15 | | 11x+61=Ax+Bx+5A+8B | | 6-2y=10-8y+6y | | x-22x+2y=4 | | 11x+61=Ax+Bx+5A+8A | | (x-2)2x+2y=4 | | (-8)-14= | | 6g-4h=-2g+28 | | 2m-7n-4m+9n= | | 5p+8m=-10p+3 | | 4x-8y=2x+10 | | 8-n(2)=20 | | 81-x^4=0 | | 5N^3+2N^2+15N=0 | | 10+x-(2-3x)=4 | | 1080=26x+95 | | 2t+1=-1 |

Equations solver categories